2022
DOI: 10.11158/saa.27.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Updated checklist of the hard ticks (Acari: Ixodidae) of Egypt, with notes of livestock host and tick-borne pathogens

Abstract: The checklist of hard ticks in Egypt was updated with 44 tick species. Hosts, geographical distribution, and pathogens of the hard ticks collected from domestic animals were also reviewed based on our investigation and published data from 1915 to 2021. Lower Nile Valley (including the Delta) had the largest number of hard tick species from domestic animals with 20 different species. Cattle and dromedary camels were infested by 19 hard tick species. Nineteen described species from livestock in Egypt were confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Phylogenetic analysis showed relatedness between the study sample sequences and the same species from other African countries such as Sudan, Guinea-Bissau, and Uganda. Although imported cattle to Egypt were reported to be infested by A. lepidum and A. variegatum in previous studies(Robinson 1926;Hoogstraal 1956;Okely et al 2022), no Amblyomma species were collected from cattle during this study. Our results and previous studies suggest that native cattle were not infected by Amblyomma spp.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Phylogenetic analysis showed relatedness between the study sample sequences and the same species from other African countries such as Sudan, Guinea-Bissau, and Uganda. Although imported cattle to Egypt were reported to be infested by A. lepidum and A. variegatum in previous studies(Robinson 1926;Hoogstraal 1956;Okely et al 2022), no Amblyomma species were collected from cattle during this study. Our results and previous studies suggest that native cattle were not infected by Amblyomma spp.…”
mentioning
confidence: 70%
“…The genus Amblyomma is represented by approximately 138 species worldwide, ≈ 20% of all world tick species (Guglielmone et al 2015;Okely et al 2022). Species of this genus are distributed in Neotropical, Afrotropical, and Australasian regions, with highest diversity in the Neotropical region (Barker and Burger 2018;Horak et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ticks with anomalies are found during studies, which do not have tick anomalies in focus, therefore, it is important to be observed and described. Although several tick surveillance programs have been implemented in various ecological zones throughout the country (Okely et al 2022 ), this is the first report on morphological abnormalities in ticks from Egypt.…”
Section: Discussionmentioning
confidence: 91%
“…Gynandromorphic Hyalomma dromedarii with the pieces of male scutum (marked with white arrows) embedded in female alloscutum, dorsal view (A); the male characters on the left side with the presence of a posterior ridge, paramedian groove, and lateral groove, dorsal view (B) and described. Although several tick surveillance programs have been implemented in various ecological zones throughout the country (Okely et al 2022), this is the first report on morphological abnormalities in ticks from Egypt.…”
Section: Figmentioning
confidence: 96%